Muscle fiber capillarization as determining factor on indices of insulin sensitivity in humans. Issue 10 (26th May 2017) - Snijders, Tim; Nederveen, Joshua P.; Verdijk, Lex B.; Houben, Alfons J. H. M.; Goossens, Gijs H.; Parise, Gianna; van Loon, Luc J. C.
Abstract: To investigate the association between muscle fiber capillarization and indices of insulin sensitivity in healthy older adults. A skeletal muscle biopsy was taken from the m . vastus lateralis of 22 healthy (nondiabetic) male older adults. In addition, all participants underwent an Oral Glucose Tolerance Test (OGTT). Muscle fiber capillarization was assessed by immunohistochemistry. Participants were divided into a group with relatively low (LOW) or high (HIGH) muscle fiber capillarization (capillary‐to‐fiber perimeter exchange (CFPE) index), based on the median value for the entire group. All participants were healthy, nonobese, and had a normal glucose tolerance, according to the individual OGTT results. Whereas no differences in blood glucose concentrations were observed between groups during the OGTT, the postprandial increase in plasma insulin concentrations was significantly greater in the LOW compared to the HIGH muscle fiber capillarization group ( P < 0.05). Skeletal muscle fiber capillarization may determine insulin sensitivity in humans. Abstract : The present study findings suggest that skeletal muscle tissue capillarization represents an important factor in glucose tolerance, and determine whole‐body insulin sensitivity in the older population.